Novel regulatory variant detected on the VKORC1 haplotype that is associated with warfarin dose. (August 2016) - Cavalli, Marco; Pan, Gang; Nord, Helena; Eriksson, Niclas; Wadelius, Claes; Wadelius, Mia
Aim: Warfarin dose requirement is associated with VKORC1 rs9923231, and we studied whether it is a functional variant.Materials & methods: We selected variants in linkage disequilibrium with rs9923231 that bind transcription factors in an allele-specific way. Representative haplotypes were cloned or constructed, nuclear protein binding and transcriptional activity were evaluated.Results: rs56314408C>T and rs2032915C>T were detected in a liver enhancer in linkage disequilibrium with rs9923231. The rs56314408–rs2032915 C-C haplotype preferentially bound nuclear proteins and had higher transcriptional activity than T-T and the African-specific T-C. A motif for TFAP2A/C was disrupted by rs56314408T. No difference in transcriptional activity was detected for rs9923231G>A.Conclusion: Our results supported an activating role for rs56314408C, while rs9923231G>A had no evidence of being functional.